2009
DOI: 10.1108/10610420910989721
|View full text |Cite
|
Sign up to set email alerts
|

Corporate brand management in higher education: the case of ERAU

Abstract: Purpose -There is evidence in the literature that organizations struggle to formulate and implement their corporate branding strategies. This paper aims to provide an overview of the corporate brand building process in higher education. Design/methodology/approach -A qualitative methodology was used in this study. A single case study of a private American university was used to gather information about their corporate brand building process. University administrators and documents were used to gain insights in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 37 publications
3
100
0
5
Order By: Relevance
“…The idea of belonging aligns with the corporate branding approach (Curtis et al, 2009). Unlike other purchase decisions, a student signing up for a degree is effectively signing up for a lifelong relationship with the university, as they will always have that university's name linked with their own.…”
Section: Heis As Corporate Brandsmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea of belonging aligns with the corporate branding approach (Curtis et al, 2009). Unlike other purchase decisions, a student signing up for a degree is effectively signing up for a lifelong relationship with the university, as they will always have that university's name linked with their own.…”
Section: Heis As Corporate Brandsmentioning
confidence: 99%
“…Mazzarol and Soutar (2012) and Sultan and Wong (2012) discuss the competitive market of higher education and argue for the importance of image and reputation to frame a university's offering, while Curtis et al (2009) postulate that HEIs feel these market pressures in many different nations. Casidy (2013) provides empirical evidence to demonstrate that a clear brand orientation works to a university's advantage.…”
Section: Social Media and Higher Education Institution (Hei) Brandingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the field we are dealing with, that of HE, in the early 1980s Keller (1983) predicted a growing importance of the marketing application in the sector and, since then, several authors have agreed on the desirability of adopting a marketing perspective (for instance , Çetin 2004;Flavián and Lozano 2004;Ma and Todorovic 2011;Filip 2012;Stimac and Simic 2012;Kalenskaya et al 2013;Tanrikulu and Gelibolu 2015;Tran et al 2015). Further, a gradual increase is observed in the number of universities that incorporate marketing principles and practices within management (Kotler and Fox 1995;Yavas and Shemwell 1996;Newman 2002;Soutar and Turner 2002;Hemsley-Brown and Oplatka 2006;Hayes 2007;Liao 2008;Curtis et al 2009;Wasmer and Bruner II 2009;Hemsley-Brown and Oplatka 2010;Cardoso et al 2011;Filip 2012;García Sanchis 2012;Kalenskaya et al 2013;Tran et al 2015) and that show more concern about becoming market oriented (Mavondo et al 2008;Ressler and Abratt 2009;Cardoso et al 2011;Gattermann et al 2012;Kalenskaya et al 2013;Tran et al 2015), especially among private institutions (Bardo et al 1990;Maringe and Gibbs 2009;Cardoso et al 2011).…”
Section: The Holistic Marketing Orientation As a University Manage-mementioning
confidence: 99%
“…Aware of the greater intensity of competition, universities have shown more interest in developing and maintaining a favourable distinctive image or reputation (Curtis et al 2009;Maringe and Mourad 2012), since " [it] has been identified as one of the main factors affecting higher education (HE) choice (Hemsley-Brown and Oplatka 2016, p.113)". To this end, many have responded by concentrating their efforts on renewing their training programmes and trying to improve quality (Bugandwa 2009).…”
Section: Introductionmentioning
confidence: 99%